Pengaruh Work Life Balance, Motivasi Kerja, Disiplin Kerja Terhadap Kinerja Karyawan Pada Pt Star Concord Indonesia Cabang Surabaya - Tasya Angela Putri; Shinta Setia (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to examine the Effect of Work Life Balance, Work Motivation, and Work Discipline on Employee Performance. This study uses employee performance (Y) as the dependent variable and this study uses work life balance (X1), work discipline (X2), work motivation (X3) as independent. The population in this study are permanent employees of PT. Star Concord Indonesia Surabaya branch. The sampling technique to be used is simple probability sampling. The sample consisted of 50 employees aged 24-40 years and a minimum of one year of service. Analysis using Structural Equation Modeling (SEM) with the help of Warp PLS 8.0. The results of the study show that work life balance has a significant positive effect on employee performance, work motivation has a significant positive effect on employee performance, work discipline has no effect on employee performance. Keywords: Work Life Balance, Work Motivation, Work Discipline.